Single Donor Transistors with Nanochannels and Role of Dielectric Confinement (Bulletin of Pure and Applied Sciences – Physics, 2020)
We have studied Single donor transistors with designed nanochannels in which the  tunnel barrier height is enhanced due to dielectric confinement. For single electron  tunneling effects the charging energy is significantly large. Which is a first limiting  factor for shallow dopants? At high temperatures, thermally activated transport  became quickly dominant. We have found that at high temperature operation of  electron tunneling occurred via a single donor. We have found that the single dopant  devices operating at room temperature paving the way for practical applications  based on individual dopant atom in silicon nanodevices. We have also found that in  nanopatterned channel transistors, single electron tunneling via individual positive  donors was observed at elevated temperatures. The obtained results were found in  good agreement with previously obtained results.